2013
DOI: 10.5811/westjem.5.15279
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Successful Incentive-based Ultrasound Credentialing Program for Emergency Physicians

Abstract: Introducion:With the rapid expansion of emergency ultrasound, resident education in ultrasound has become more clearly developed and broadly integrated. However, there still exists a lack of guidance in the training of physicians already in practice to become competent in this valuable skill. We sought to employ a step-wise, goal-directed, incentive-based credentialing program to educate emergency physicians in the use of emergency ultrasound. Successful completion of this program was the primary outcome.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…The low credentialing success (19.7%) of the Cape Town clinical ultrasound training programme is concerning considering the time and resource investments made. The rate is significantly lower than six peer international training programmes, whose credentialing success ranged between 30.2 and 100%; however, all six studies were conducted in high resource settings [ 10 12 , 14 16 ]. Of more concern, Cape Town’s credentialing success was most likely an overestimate of the national study population since the Cape Town sample represented 50% of the study population but also accounted for 90% of the national credentialing success.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The low credentialing success (19.7%) of the Cape Town clinical ultrasound training programme is concerning considering the time and resource investments made. The rate is significantly lower than six peer international training programmes, whose credentialing success ranged between 30.2 and 100%; however, all six studies were conducted in high resource settings [ 10 12 , 14 16 ]. Of more concern, Cape Town’s credentialing success was most likely an overestimate of the national study population since the Cape Town sample represented 50% of the study population but also accounted for 90% of the national credentialing success.…”
Section: Discussionmentioning
confidence: 93%
“…All these training programmes had low credentialing success rates (30.2 to 44.9%) but still higher than Cape Town’s. Training programmes that divided their training capacity between only a few hospitals with a proper trainer and ultrasound machine access had the highest credentialing outcomes (67.7 to 100%) [ 12 , 16 ]. Their trainees reported logistical barriers, related to their training programme curriculum, as their highest perceived barriers to credentialing.…”
Section: Discussionmentioning
confidence: 99%
“…However, if no EUS fellowship program is present, there is a greater likelihood that the QA process is not being conducted on a weekly basis. However, studies have shown that a weekly QA process is the optimal method to provide feedback, performance improvement, and assurance that ultrasounds are being performed and interpreted correctly [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike residents, attendings are more likely to have established practice patterns that make POC US implementation more difficult, they may have less time to devote to voluntary didactic learning, and their role during clinical shifts differs such that learning a new clinical skill like POC US during a shift may be more challenging. 4 …”
Section: Introductionmentioning
confidence: 99%